Postinflammatory rupture of right coronary artery ostium complicating Behçet disease. Issue 10 (21st July 2022) - Fiore, Antonio; Piscitelli, Mariantonietta; Rabia, Amel; Derbel, Haytham; Bergoend, Eric; Avtaar Singh, Sanjeet S.; Nappi, Francesco
Abstract: Introduction: Behçet disease (BD) is a chronic relapsing inflammatory disease of unknown etiology, characterized by variable clinical manifestations. Methods: A 28‐year‐old woman with BD Cardiovascular and Bipolar Disorder underwent emergency surgical treatment of ascending aortic pseudoaneurysm for ruptured right coronary ostium.A modified Bentall procedure with tricuspid annuloplasty, surgical thrombectomy, and a single coronary artery bypass using a saphenous vein graft was performed. A biological prosthesis was used initially but subsequently deteriorated. We then successfully performed a valve‐in‐valve (ViV) transcatheter aortic valve implantation (TAVI). Results: The postoperative recovery was uneventful and at follow‐up, two years post valve procedure, the patient was completely symptom‐free. She remains under long‐term medical surveillance. Conclusion: The management of BD with cardiac involvement must be led by a multidisciplinary team.